Filtration of random solutions of a system of linear difference equations with coefficients depending on a Markov chain - Lapshin, A. L. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We solve the problem of the estimation of a random state for a system with discrete time that is described by a system of linear difference equations with coefficients depending on a finite-valued Markov chain.